The Government's Response to Workers' Rights Violations at PT Freeport Indonesia: An Analysis from the Perspective of Dependency Theory - Astuti, Vera; Purnamasari, Niken; Benteng Buana Muslim, Bintang Lazuardi (Indonesian Journal Publisher, 2024)
This study examines the Indonesian government's response to labor rights violations committed by PT Freeport Indonesia (PTFI) through the perspective of dependency theory. This theoretical framework highlights the asymmetrical relationship between developing and developed countries that often leads to resource exploitation in developing countries. The PTFI case in 2017 involved the unilateral termination of employment of 8,300 workers without clarity on their rights, accompanied by permanent dismissal contrary to labor regulations. Using the literature review method, this study analyzes existing studies related to government policies in labor protection. The findings of the study show that the government has taken various steps, including forming a supervisory team, mediating negotiations, and providing social security assistance to affected workers. This research emphasizing the need for concrete actions to reduce Indonesia's dependence on foreign investment and strengthen labor protection regulations.